Crime scene documentation : preserving the evidence and the growing role of 3D laser scanning - Galvin, Robert (Abingdon, Oxon ; Boca Raton, FL : CRC Press, 2021)
"When a criminal act or vehicle crash occurs, most often a local law enforcement agency responds and is responsible for to both investigating the scene and documenting it. It is critical that scene evidence is collected and recorded efficiently, as the scene can quickly change. The sooner evidence can be collected, reviewed, and analyzed, often the better an understanding investigators will have as to how and why the incident occurred. Crime Scene Documentation: Preserving the Evidence and the Growing Role of 3D Laser Scanning demonstrates at length the value of laser scanning through the use of numerous case studies of investigators who have utilized various 3D technologies and laser scanning to document scenes. Thorough and accurate scene documentation is an essential function at a science and proves particularly valuable in courtroom presentations to help jurors understand a crime or accident's likely chain of events. The more advanced a scene documentation method is, the better it can be utilized to capture details that will lead to optimal scene diagramming. Currently, 3D laser scanning is the most advanced method of scene documentation available, capturing detailed and realistic digital scans-and captures scenes in their entirety-yielding a permanent representation of the scene for study and analysis at any time, even years after a crime scene has vanished. The book explains current technology, the latest advances, and how to best utilize the technology. The case examples come from various applications , from tools to programs, can help crash scene investigators understand how scanning can improve scene documentation, provide better and more evidence details, and build more credible diagrams that possibly may be used in court presentations to help support a case. Key features: Describes 3Dscene recording methods in use and how well they work Outlines the variables and inherent challenges associated with documenting crime and crash scenes Illustrates the positive, and dramatic, impact of having a well-documented scene, particularly in the courtroom Explores how 3D laser scanning has vastly changed the way and extent to which crime and crash scenes can be captured accurately and completely, and subsequently analyzed Explains how laser scanning is highly flexible and presents strategies to integrate it into other crime scene incident recording techniques and technologies Crime Scene Documentation details the many benefits of 3D laser scanning technology relative to its reliability and accuracy as well as the multiple case scenarios in which it can be used. The book serves as an invaluable resource to crime scene technicians, investigators, and reconstructionists on the best ways to document a crime or crash scene"--
OCLC-licensed vendor bibliographic record.
Keywords: Criminal investigation -- Methodology; Three-dimensional imaging; LAW / Criminal Law / General; LAW / Forensic Science; SOCIAL SCIENCE / Criminology